Primary antifungal prophylaxis: decrease of invasive fungal disease incidence and reduction of risk factors in haematological patients in a 5‐year retrospective study. Issue 6 (12th June 2018) - Li, Yan; Liu, Mingjuan; Zhai, Bing; Zhao, Xiaoli; Wang, Lijun; Li, Honghua; Wang, Shuhong; Zhu, Haiyan; Wang, Quanshun; Gao, Chunji; Huang, Wenrong; Yu, Li
Abstract: Background: Invasive fungal disease (IFD) is a major cause of morbidity and mortality in patients with haematological malignancies. Aim: To evaluate the efficacy and rationality of primary antifungal prophylaxis (PAP) in a 5‐year real‐life setting and choose an appropriate PAP strategy. Methods: Clinical data of patients were retrospectively reviewed and IFD was diagnosed using the revised diagnostic criteria. The efficacy of PAP and the risk factors for IFD, especially the rationality of PAP, were evaluated. Results: Of the 1340 patients enrolled, 749 patients received PAP (55.9%), and IFD occurred in 157 patients: 51 (6.8%) in the PAP group and 106 (17.9%) in the non‐PAP group ( P = 0.000). The IFD‐related mortality was 10.1 and 29.7% in the PAP group and non‐PAP group ( P = 0.000) respectively. PAP was an independent protective factor for IFD (odds ratio = 0.183, 95% confidence interval: 0.122–0.274, P = 0.000) and could reduce the effect of risk factors, such as allogeneic haemopoietic stem cell transplantation, prolonged neutropenia and corticosteroid. The IFD incidence was not significantly different among different PAP regimens and PAP start time subgroups, and it was lowest (4.2%) when PAP started after a short period of neutropenia (1–10 days). Conclusion: PAP is necessary and efficient to prevent IFD in haematological patients, and the real‐life PAP strategy is reasonable. Different drugs can be chosen, and it is better to start PAP as soon as neutropenia begins.